2014
DOI: 10.1002/2014gc005509
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of plate coupling, fate of subduction fluids, and modes of arc magmatism in Cascadia, inferred from magnetotelluric resistivity

Abstract: Five magnetotelluric (MT) profiles have been acquired across the Cascadia subduction system and transformed using 2-D and 3-D nonlinear inversion to yield electrical resistivity cross sections to depths of 200 km. Distinct changes in plate coupling, subduction fluid evolution, and modes of arc magmatism along the length of Cascadia are clearly expressed in the resistivity structure. Relatively high resistivities under the coasts of northern and southern Cascadia correlate with elevated degrees of inferred plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
110
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 128 publications
(321 reference statements)
17
110
0
Order By: Relevance
“…Atg antigorite serpentinite, CPx clinopyroxene, OPx orthopyroxene, and Ol olivine. Olive symbols olivine aggregate and dark green symbols pyroxene-rich peridotite resolution of 2D electrical conductivity images has greatly improved (Wannamaker, et al 2014;Worzewski, et al 2011) with imaging of fluid paths that can be compared with seismic tomography. Typical values of conductivity range between 10 −3 and 10 −4 and 1 S.m 1 , the lower values being defined by the background sensitivity in cold and fluid-poor regions, and the highest observed in zones where fluids and melts are abundant.…”
Section: Magnetotelluricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atg antigorite serpentinite, CPx clinopyroxene, OPx orthopyroxene, and Ol olivine. Olive symbols olivine aggregate and dark green symbols pyroxene-rich peridotite resolution of 2D electrical conductivity images has greatly improved (Wannamaker, et al 2014;Worzewski, et al 2011) with imaging of fluid paths that can be compared with seismic tomography. Typical values of conductivity range between 10 −3 and 10 −4 and 1 S.m 1 , the lower values being defined by the background sensitivity in cold and fluid-poor regions, and the highest observed in zones where fluids and melts are abundant.…”
Section: Magnetotelluricsmentioning
confidence: 99%
“…Magnetotellurics made great improvements in providing more accurate pictures of subduction zones from early studies that depicted rough limits between compartments of a few tens of kilometers to recent studies that give resolution of a few kilometers (Wannamaker, et al 2014;Worzewski, et al 2011). In the forearc region, the most prominent structures are high-conductivity zones that are located near the limit between the serpentinized mantle and the base of the overriding plate (Fig.…”
Section: Fluid Composition From Magnetotelluric Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Kohl & Rybach 1996), the dynamics of electric resistivity, covering several orders of magnitudes compared to typical crustal rock, characterize mid-crustal conductors (e.g. Unsworth et al 2004;Hill et al 2009;Wannamaker et al 2014). The origin of these electric conductors has early been attributed to graphite (Frost et al 1989;Jödicke 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of these electric conductors has early been attributed to graphite (Frost et al 1989;Jödicke 1992). More recently, links to aqueous fluids and secondary minerals in fault zones (Korja et al 2008;Brasse et al 2009;Weckmann et al 2012), to partial melt (Unsworth et al 2005;Hill et al 2009), and to metamorphic processes (Wannamaker et al 2014;Zhang et al 2015) have been discussed. Worldwide, it is observed that these conductors have an upper depth limit near the brittle-ductile transition (Jones 1992;Jiracek 1995).…”
Section: Introductionmentioning
confidence: 99%